Figures of Speech and Imagery in The Digital Geguritan Anthology: A Stylistic Study - Husein Erwinsyah; Suwardi Endraswara; Sulis Triyono (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
Literary works are the manifestation of human thought. Geguritan is one of the interesting but complex literary works. Figures of speech and imagery are widely used in geguritan. This study aims to analyze figures of speech and imagery in the geguritan anthology in the GEGURITAN TEMBANG ATI Facebook group. This study uses a stylistic approach with a qualitative descriptive method. The data sources for the study were two geguritan entitled